EFFECT OF USING GEOGEBRA ON 7TH CLASS STUDENTS UNDERSTANDING IN LEARNING GEOMETRIC CONSTRUCTION PROBLEMS - Ablyakieva А.; Omarbayeva Б.; Bostanov Б.; Adiyeva А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The aim of this study was to investigate the effect of using the Geogebra program on the performance in teaching the topic "Geometric construction problems " in the 7th grade geometry subject was considered. The quasi-experimental method was used during the research, and students of the 7th grade of general education school no129 took part in it. The students were divided into two groups. In the first group was an experimental group taught using the computer interactive Geogebra program, and in the second groups were a control group using traditional teaching. During the research, pre-test and post-test were taken from students. The difference between the pre-test and post-test of the study will determine the effect of Geogebra on students’ academic performance. In addition, a survey was taken from students about the impact and benefits of the Geogebra program, and the results of the survey were discussed. As a result, the usefulness, impact, and effectiveness of the Geogebra program (p < 0.05) in teaching the topic "Geometric construction problems" were determined.